The relationship between the possibility of applying electronic banking and the readiness of commercial banks in Sulaymaniyah Governorate - Chia Mohamed Hassan; Ismail Mohammed Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The aim of this study is to identify the possibility of applying electronic banking and the prepareess of the commercial banks in the province of Sulaymaniyah. It does also measure the impact of the possibility of applying electronic banking on the organizational variables such as availability of technological resources, availability of qualified human resources and expected return by applying electronic banking. Moreover, it intends to determine the nature of the relationship between the possibility of applying electronic banking and the organizational variables in the banks under study. The sample of the study covered all employees in the commercial banks in the province of Sulaymaniyah. The result of the study indicated a statistically significant relationship at the level of 0.05 between the (availability of technological resources, availability of qualified human resources, expected return on application of electronic banking systems) and levels of application of e-banking systems. On the other hand, the results of the study showed no statistically significant differences at the significance level 0.05 on the levels of application of electronic banking systems, based on the personal attributes of study sample (education level, years of service, sex). The study recommends expanding the use of technology by providing necessary information that customers need it when electronic banking services operate. This is due to adopting specific marketing strategies, aiming at increasing awareness of current and potential customers about electronic services, their importance and how to benefit from them. Moreover, it is important to have a solid electronic infrastructure that suits the adoption of electronic banking services and develop a control-tool to measure expected returns when electronic banking is established. It also important to consider the benefits and costs for each service prior to offering.